The efficacy of chelated micronutrient fertilisers in tomato cultivation - Volodymyr Sievidov; Oksana Serhienko; Ivan Lebedynskyi; Igor Sievidov (Наукові горизонти)
The study aimed to investigate the impact of foliar fertilisation on the growth and development processes of tomato plants of different maturity groups throughout the entire growing season, as well as on overall yield levels. The research, conducted during 2018-2021 in film greenhouses at the experimental site of the State Biotechnological University, located in the south eastern part of the Left-Bank Forest-Steppe of Ukraine, examined the F1 indeterminate tomato hybrids Berberana (early maturity) and Bostina (mid-early maturity). The results demonstrated that foliar fertilisation accelerated plant development phases compared to the untreated control variant. The treated plants exhibited the most vigorous development during the budding phase, with bud formation occurring two to four days earlier than in the control group. It was observed that plants subjected to foliar fertilisation had superior biometric indicators during the mass flowering phase. The differences in primary biometric indicators during the mass flowering phase, depending on the application of foliar fertilisation, ranged from 3% to 18%. During the mass fruiting phase, these differences varied from 2% to 9% with a single treatment and from 5% to 17% with three treatments. Furthermore, the experiment involving three treatments demonstrated the highest monthly yield increases, exceeding the control by 12% to 21%. The findings indicated that the most effective treatment was the application of chelated micronutrient fertilisers three times, resulting in a yield increase of 17.5% (2.8 kg/m2 ) for the Berberana hybrid and 14.8% (2.2 kg/m2 ) for the Bostina hybrid compared to the control. These yield improvements provide producers with an opportunity for increased profit. The practical significance of this study lies in identifying the effects of foliar fertilisation on tomato yield in protected soil conditions. Additionally, the study established optimal and scientifically justified rates and application timings for complex fertilisers with chelated micronutrients. These measures ensure the maximum realisation of the crop’s genetic potential